Budd–Chiari syndrome: Focus on surgical treatment. Issue 2 (22nd July 2016) - Hidaka, Masaaki; Eguchi, Susumu
Abstract : Budd–Chiari syndrome (BCS) is caused by an obstruction in the hepatic venous outflow tract at various levels from small hepatic veins to the inferior vena cava (IVC) due to thrombosis or fibrous sequelae. This rare disease mainly affects young adults. Risk factors have been identified and patients often have multiple risk factors. Myeloproliferative diseases of atypical presentation account for nearly 50% of patients in Europe and North America countries. Multistep management is required for such patients. Interventional revascularization and transjugular intrahepatic portosystemic shunt procedure are indicated after initial anticoagulation therapy, whereas IVC plasty using a patch graft is indicated for obstruction of the IVC. Liver transplantation (LT) is usually indicated as a treatment for liver failure despite various treatments. The outcomes of LT are good, with a 5‐year survival after LT of nearly 70%.